2005
DOI: 10.1007/11566465_107
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Realistic Tissue Reflectance Modelling for Minimally Invasive Surgical Simulation

Abstract: Abstract.Computer-based simulation is an important tool for surgical skills training and assessment. In general, the degree of realism experienced by the trainees is determined by the visual and biomechanical fidelity of the simulator. In minimally invasive surgery, specular reflections provide an important visual cue for tissue deformation, depth and orientation. This paper describes a novel image-based lighting technique that is particularly suitable for modeling mucous-covered tissue surfaces. We describe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Therefore, a normal map disrupts the specular component computing, while an additional texture map produces colour for blending with the surface original colour, in real time (see Figure ). In 2005, this technique was evaluated by a group of naive volunteers and experts surgeons in a bronchoscopy surgery context [E*05]. The visual results show improvements when compared with standard Phong‐like models for organic tissue representation.…”
Section: General Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a normal map disrupts the specular component computing, while an additional texture map produces colour for blending with the surface original colour, in real time (see Figure ). In 2005, this technique was evaluated by a group of naive volunteers and experts surgeons in a bronchoscopy surgery context [E*05]. The visual results show improvements when compared with standard Phong‐like models for organic tissue representation.…”
Section: General Approachesmentioning
confidence: 99%
“…A standard texture rendering with Blinn–Phong lighting model (left) and a result computed by roughness and mucous layer colour mapping (right). Source: [E*05].…”
Section: General Approachesmentioning
confidence: 99%
“…The coefficients of the function are determined by constraining to satisfy the interpolation conditions and solving the following linear system of equations: (9) where , and is a matrix with the deformed points. Intuitively, measures the effect of the th control point on the transformation at the th control point.…”
Section: Mesh Warping Using Radial Basis Functions (Rbfs)mentioning
confidence: 99%
“…To overcome this problem, the reliance on patient specific data for building anatomical models both in terms of biomechanical fidelity and photorealism has attracted extensive interests in recent years [6], [7]. Existing work has already demonstrated that by fusing real-bronchoscopy video with three-dimensional (3-D) tomographic data of the same patient, it is possible to generate photorealistic models that allow high fidelity, patient specific bronchoscope simulation [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Jensen et al [15] use a subsurface scattering model with a raytracer to achieve good results. ElHelw et al [16] describe their method in improving realism with polygonal models in a surgical simulation, which highlights the importance of using specular variation with multitexturing to provide a more natural looking wet surface, which in their case is tissue with a thin, transparent mucus as seen through a bronchoscope.…”
Section: Related Workmentioning
confidence: 99%